Static and fatigue behaviour of glass-fibre-reinforced polypropylene composites - Ferreira, J. A. M. (1999)
This paper is concerned with fatigue of polypropylene/glass-fibre thermoplastic composites produced from a bi-directional woven cloth mixture of E glass fibres and polypropylene fibres. The latter becomes the matrix after the application of heat and pressure. This composite was manufactured with a fibre volume fraction Vf of 0.338. The effect of layer design on the static and fatigue performance was investigated. The S-N curves, the rise in the temperature of the specimens during the tests and the loss of stiffness, were obtained and discussed. The loss of stiffness was related to the rise of temperature and stress release observed in the material. The effect of load rate on the static properties was also studied and discussed accordingly.